Meningkatkan Peran Keilmuan Desain Produk Bagi Kemampuan Dasar Mahasiswa Fakultas Ilmu Rekayasa Universitas Paramadina Melalui Evaluasi Pembelajaran Mata Kuliah Berpikir Desain - Ardian, Noel Febry; Samri, Ira Handayani; Putri, Farahiyah Inarah (Universitas Pembangunan Jaya, 2025)
This research is an evaluation of the learning of the Design Thinking course. This evaluation aims not only to improve the quality of the curriculum and learning process, but also to find ways to strengthen the interdisciplinary approach so that learning is more easily understood by students outside of product design. This research was conducted through a survey using a questionnaire to assess the attractive, challenging, and beneficial aspects of learning, as well as students' understanding of the principles of human-centeredness and collaboration. The results show that the product design discipline has popular and challenging materials, such as ideation with brainstorming and prototyping stages. This indicates good acceptance of learning materials that are not too focused on this discipline. Students feel that this learning is relevant to career development. This research recommends improving teaching materials and methods according to the needs of the world of work and increasing active involvement in group collaboration. These results also strengthen the scientific contribution and role of the Design Thinking course as a distinctive feature of faculty graduatesKeywords:Design Thinking; Learning Evaluation; Product Design